Changes in genetic and environmental influences on depressive symptoms across adolescence and young adulthood. - Lau, J; Eley, T (2006)
BACKGROUND: Depression rises markedly in adolescence, a time when increased and new genetic influences have been reported. AIMS: To examine'new'and'stable' genetic and environmental factors on depressive symptoms in adolescence and young adulthood. METHOD: A questionnaire survey investigated a sample of twin and sibling pairs at three time points over an approximately 3-year period. Over 1800 twin and sibling pairs reported depressive symptoms at the three time points. Data were analysed using multivariate genetic models. RESULTS: Depressive symptoms at all time points were moderately heritable with substantial non-shared environmental contributions. Wave 1 genetic factors accounted for continuity of symptoms at waves 2 and 3. 'New'genetic effects at wave 2 also influenced wave 3 symptoms. New non-shared environmental influences emerged at each time point. CONCLUSIONS: New genetic and environmental influences may explain age-related increases in depression across development.